LFA-1 Controls Th1 and Th17 Motility Behavior in the Inflamed Central Nervous System - Dusi, Silvia; Angiari, Stefano; Pietronigro, Enrica Caterina; Lopez, Nicola; Angelini, Gabriele; Zenaro, Elena; Della Bianca, Vittorina; Tosadori, Gabriele; Paris, Francesca; Amoruso, Antonella; Carlucci, Tommaso; Constantin, Gabriela; et al. (Frontiers in Immunology, 2019)
Leukocyte trafficking is a key event during autoimmune and inflammatory responses. The leptomeninges and cerebrospinal fluid are major routes for the migration of encephalitogenic T cells into the central nervous system (CNS) during experimental autoimmune encephalomyelitis (EAE), the animal model of multiple sclerosis, and are sites of T cell activation before the invasion of CNS parenchyma. In particular, autoreactive Th1 and Th17 cell trafficking and reactivation in the CNS are required for the pathogenesis of EAE. However, the molecular mechanisms controlling T cell dynamics during EAE are unclear. We used two-photon laser microscopy to show that autoreactive Th1 and Th17 cells display distinct leptomeningeal motility behavior in the spinal cord of mice immunized with the myelin oligodendrocyte glycoprotein peptide MOG35-55. Although both T cell populations displayed fast random movement during the pre-clinical phase, Th1 cells showed a strong directional bias at the disease peak, moving in a straight line and covering long distances, whereas Th17 cells exhibited more constrained motility. The analysis of T cell dynamics during different disease phases suggested progressive antigen-dependent activation, with the chronic phase characterized by low motility and stable cell–cell contacts. The dynamics of both Th1 and Th17 cells were strongly affected by blocking the integrin LFA-1, which interfered with the deformability and biomechanics of Th1 but not Th17 cells. The intrathecal injection of a blocking anti-LFA-1 antibody at the onset of disease significantly inhibited EAE progression and also strongly reduced neuro-inflammation in the immunized mice. Our results show that LFA-1 plays a pivotal role in T cell motility during EAE and suggest that interfering with the molecular mechanisms controlling T cell motility can help to reduce the pathogenic potential of autoreactive lymphocytes.